Main methodological issues in the study of job stress in college staff: A systematic review - Rojas-Solís, José Luis (2020)
Introduction: Research about of job stress at university contexts has not been exempt from conceptual and methodological difficulties. Objective: analyze the main methodological and instrumental aspects in studies published between 2010 and 2019, on job stress in professor, administrative and support staff working in Latin American universities. Method: following the suggested by the PRISMA model, it was consulted the databases: LA Reference, Dialnet, Scopus, EBSCO and Web of Science, obtaining 258 papers that, after a debugging process, derivated 6 studies for their final review. Results: the results show that all the studies were quantitative, with non-experimental and cross-sectional designs, and with descriptive scopes. In addition, the use of 15 instruments that mainly assess work stress and occupational risk factors was detected. Theoretical and methodological implications derived from the findings are discussed.